2019
DOI: 10.3390/molecules24173023
|View full text |Cite
|
Sign up to set email alerts
|

Using Bee Products for the Prevention and Treatment of Oral Mucositis Induced by Cancer Treatment

Abstract: Oral mucositis is one of the most frequent complications after chemotherapy or radiotherapy or a combination of both. There is no standard therapy for its prevention or treatment. Considering that some bee products have been found to be of value in this situation, we decided to analyze the scientific literature on the subject. Scientific publications on bee products were identified by a literature search on Pubmed, Scopus and Google Scholar. There is a lot of evidence regarding the use of honey for oral mucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
1
27
0
4
Order By: Relevance
“…RJ is important in maintaining the quality of life and suppresses adverse events in patients undergoing anti-cancer therapies. RJ protects against organ dysfunctions and discomfort caused by various cancer therapies (6,7). We have previously reported that RJ suppresses the adverse events caused by TKIs in patients with RCC (8).…”
Section: Introductionmentioning
confidence: 99%
“…RJ is important in maintaining the quality of life and suppresses adverse events in patients undergoing anti-cancer therapies. RJ protects against organ dysfunctions and discomfort caused by various cancer therapies (6,7). We have previously reported that RJ suppresses the adverse events caused by TKIs in patients with RCC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments based on natural products are regarded as alternative or complementary in certain oral conditions. Indeed, products from the hive such as honey and royal jelly, are used to treat mucositis and other disorders of the oral mucosa [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Las propiedades antibacterianas y antiinflamatorias de los elementos derivados de la miel, sumado a su capacidadpara desbridar, estimular el crecimiento de los tejidos, controlar el dolor y minimizar las cicatrices, podría argumentar su utilización en el manejo y tratamiento de la MO. La revisión sistemática realizada por Münstedt & Männle (2019), evaluaron la prevención y el tratamiento de la MO a base de productos de abejas en pacientes sometidos a tratamientos antineo-plásicos. Los resultados sugieren la utilización de 20 ml de miel 15 minutos antes y después de la RT y una tercera dosis 6 h después.…”
Section: Introductionunclassified